PENGARUH MODAL PSIKOLOGIS DAN KEPUASAN KERJA TERHADAP KINERJA MELALUI OCB DENGAN RESISTENSI PERUBAHAN DAN KOMITMEN TIM SEBAGAI VARIABEL MODERASI (Studi Pada Pegawai Setda Kabupaten Pati) - Fithri Nugrahani S., 12.5202.0106 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study examined the effect of psychological capital and job satisfaction on performance through Organizational Citizenship Behavior (OCB) with resistance to change and team commitment as moderating variables. The use of resistance to change and team commitment as a moderating variables in one study is the development of model in this research. Another development is done by combining two moderation tests and one mediation test in one of the research model. This research was conducted at Sekretariat Daerah (Setda) Kabupaten Pati. The sample used in this study was originally numbered 162 employees, but questionnaires can be returned for further analysis totaled 138. The entire results of the study support the nine hypothesises that has built. Keywords :        psychological capital, job satisfaction, performance, OCB, resistance to change, team commitment